STRATEGIC APPROACH IN FORMING MORALS AND RELIGIOUS ATTITUDES OF MUSLIM COMMUNITIES IN SOCIAL LIFE - Ali Nupiah (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The formation of morals and religious attitudes of Muslim society is very urgent to be implemented. This approach encourages Muslim communities to think actively about moral issues and in making moral decisions. Moral development according to this approach is seen as the development of levels of thinking in making moral judgments, from a lower level to a higher level. The aim of the research is to describe thoughts about strategies to shape morals and shape the religious attitudes of Muslim communities. This research is in the form of a literature study. The cognitive development approach characteristically places emphasis on cognitive aspects and their development. The type of research used in this discussion is using literature study which includes: systematic identification, analysis of documents containing information related to the study problem. So, the study here is to identify and analyze several documents or library materials according to the problem being studied. The research results show that the strategy for forming morals is by providing role models. Strategy for forming morals , namely: a person acts as a role model in his environment to evaluate moral development. Strategies for forming religious attitudes, namely: Adding Kahazana material about how to form religious attitudes, and adding Kahazana material about how to form religious attitudes. The strategy for forming religious attitudes, namely: Make notes in the muhasabah book about the formation of religious attitudes and check the notes in the muhasabah book about the formation of religious attitudes.